Bursting the bubble: Chewing gum for prevention of postoperative ileus. Issue 2 (February 2017) - Jarrett, Jennie B.
Abstract : N/A: Short V, Herbert G, Perry R, et al. Chewing gum for postoperative recovery of gastrointestinal function. Cochrane Database Syst Rev . 2015; (2):CD006506.